Scouting the desert of the real - Krevel, Mojca (ELOPE (Ljubljana), 2010)
The paper examines the legacy of the European historical Avant-Gardes from the perspective of the shift of paradigms immanent in the formation of the Postmodern epoch. The existing theories generally regard the Avant-Gardes as an unsuccessful attempt to redefine the function of art in the social, cultural and economic environment of the early 20th century. Examining the productivity and relevance of the historical Avant-Gardes from the perspective of the Avant-Pop, the first thoroughly Postmodern literary movement, I intend to show how the strategies of fragmentation and the breaking of organicity not only quintessentially defined the manner in which Modernity and its art came to an end, but how they also provided the basis for the formation of culture and art that no longer functions according to Cartesian principles.
Keywords: avantgarda; avantgarde; avant-pop; literarna gibanja; literarna teorija; literarne smeri; literary movements; literary theory; modernity; postindustrial capitalism; postindustrijski kapitalizem; postmoderna doba; postmodernity